Malaria Infection Among Pregnant Women of Abau District in Papua New Guinea - Susina Yatapya; Dwi Sarwani Sri Rejeki; Siwi Pramatama Mars Wijayanti; Radi Radi (Jurnal Kesehatan Masyarakat, 2025)
Malaria is a communicable disease that poses a serious problem in Papua New Guinea, with the country recording the highest incidence of malaria in the Asia-Pacific region each year. However, research on the risk factors for malaria in Papua New Guinea is still minimal, especially among pregnant women. This study aims to investigate the correlation between malaria incidence in pregnant women in Papua New Guinea. This study is an observational study with a cross-sectional approach conducted on 200 pregnant women from January to March 2024 in Abou District, Papua New Guinea. Data collection used questionnaires and Rapid Diagnostic Tests (RDT) to diagnose malaria infection in pregnant women. The independent variables in this study are healthcare-seeking behavior, prevention of malaria, knowledge of malaria, maternal age, marital status, occupation, education level, and residential location. The dependent variable in this study is the incidence of malaria in pregnant women. In this study, the data analysis used included univariate analysis, bivariate analysis with chi-square, and multivariate analysis with logistic regression. The results showed that the risk factors for malaria incidence in pregnant women in Papua New Guinea are malaria prevention (p-value 0.014; OR= 4.426) and healthcare-seeking behavior (p-value 0.033; OR= 4.033), meaning that pregnant women with poor malaria prevention behavior and poor healthcare-seeking behavior are four times more likely to suffer from malaria. It is hoped that pregnant women will increase their awareness of malaria prevention during pregnancy and make full use of healthcare facilities during pregnancy.